2018
DOI: 10.1016/j.socscimed.2017.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in health among nonpoor African Americans and Hispanics: The role of acute and chronic discrimination

Abstract: Racial disparities in health tend to be more pronounced at the upper ends of the socioeconomic (SES) spectrum. Despite having access to above average social and economic resources, nonpoor African Americans and Latinos report significantly worse health compared to nonpoor Whites. We combine data from the parents and children of the 1979 National Longitudinal Survey of Youth (NLSY79) to address two specific research aims. First, we generate longitudinal SES trajectories over a 33-year period to estimate the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
176
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 110 publications
(166 reference statements)
12
176
0
1
Order By: Relevance
“…This relationship was reversed among whites, where higher socioeconomic status was associated with reporting less discrimination. These results are consistent with prior literature showing that high‐SES minorities may experience greater discrimination than their lower‐SES counterparts . However, our results do not explain why this might occur.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This relationship was reversed among whites, where higher socioeconomic status was associated with reporting less discrimination. These results are consistent with prior literature showing that high‐SES minorities may experience greater discrimination than their lower‐SES counterparts . However, our results do not explain why this might occur.…”
Section: Discussionsupporting
confidence: 89%
“…Other research has found that prolonged or repeated discrimination causes major health problems over time, due to progressive wear and tear on the body's systems owing to repeated adaption to stressors (known as allostatic load and overload) . We expect that on average, discrimination will have a greater effect on the health of high‐socioeconomic status and upwardly mobile Latinos, who report experiencing greater discrimination than Latinos with lower‐socioeconomic status and those who are not upwardly mobile . Discrimination also carries major consequences for Latinos' opportunities for fair treatment in education, occupations, wages, medical care, and public safety.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Disadvantaged minority neighborhoods usually have less access to healthy foods and recreational facilities and excess advertising for products that can influence blood pressure . Further, discrimination has been shown to affect minority health, regardless of an individual's SES . Living in neighborhoods with higher SES that are also more likely to have a higher proportion of whites may expose minorities to more discrimination because of more contact with whites .…”
Section: Discussionmentioning
confidence: 99%